An Analysis of Chinas Poverty Research Based on CiteSpace - Fengyang, WU (Journal of Social Economics Research, 2019)
This paper uses CiteSpace to comprehensively grasp the situation of poverty research through the keyword co-occurrence and cluster by extracting the literature information in China during 1998-2017. The results show that the literature on poverty in China has different kinds of hotspots, which changed from rural areas, poverty alleviation and economic growth to multidimensional poverty, industrial poverty alleviation, and precise poverty alleviation. The researches mostly focus on subjects of poverty, poverty alleviation, sustainable development, and so on. This paper also finds that the number of research is huge, but the targeted research and field research is not enough. In the future, deep research on precise poverty alleviation will become a new trend.